A Novel Compact CPW-fed Octagonal-Shaped Slotted Antenna for UWB Applications - Franklin Alex Joseph, A.; Jothi, B.; Shantha Sheela, R.; Anitha, N.; Priya, S.B.; Mohan, C. (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2025)
A size-reduced CPW-fed Ultra-Wideband (UWB) octagonal-shaped patch antenna with a combination of multiple slots designed for UWB applications is proposed here. The proposed low-profile antenna includes three equalsized slots in an octagonal radiating patch. Moreover, better matching is provided by the feedline's U-shaped slots. A new combination of CPW configuration with a slotted octagonal patch increases bandwidth and reduces antenna size. The fabricated prototype of this octagonal-shaped antenna is situated on a basic FR4 substrate with a relative permittivity of εr = 4.3. The suggested antenna's substrate size measures 15 x 21 x 1.6 mm3 and has an 8.8 GHz overall bandwidth, which includes the frequency range of 3 GHz to 11.8 GHz. Variations in gain range from 1.3 to 3.2 dB, with an average overall efficiency above 81 %. This antenna has been fabricated and successfully validated with simulated results. Other features include its compactness, directivity, realized gain, and stable radiation properties across the entire operating band, proving its effectiveness.